Complement profile in microscopic polyangiitis and granulomatosis with polyangiitis: analysis using sera from a nationwide prospective cohort study. (3rd July 2020) - Fukui, S; Ichinose, K; Sada, K-E; Miyamoto, J; Harigai, M; Amano, K; Atsumi, T; Takasaki, Y; Dobashi, H; Arimura, Y; Hasegawa, H; Yuzawa, Y; et al.
Abstract : Objective: The complement cascade, especially the alternative pathway of complement, has been shown in basic research to be associated with anti-neutrophil cytoplasmic autoantibody (ANCA)-associated vasculitis (AAV). We aimed to elucidate relationships between serum complement components and clinical characteristics in AAV. Method: In a nationwide prospective cohort study (RemIT-JAV-RPGN), we measured the serum levels of C1q, C2, C3, C3b/iC3b, C4, C4b, C5, C5a, C9, factor B, factor D, factor H, factor I, mannose-binding lectin, and properdin in 52 patients with microscopic polyangiitis (MPA) and 39 patients with granulomatosis with polyangiitis (GPA). Results: The properdin level of MPA and GPA was significantly lower than that of healthy donors. The properdin level was negatively correlated with the Birmingham Vasculitis Activity Score (BVAS) (ρ = −0.2148, p = 0.0409). The factor D level at 6 months was significantly positively correlated with the Vasculitis Damage Index (VDI) at 6, 12, and 24 months (ρ = 0.4207, 0.4132, and 0.3115, respectively). Patients with a higher ratio of C5a to C5 had higher neutrophil percentage and serum immunoglobulin G levels, and significantly lower creatinine levels. Cluster analysis divided the MPA and GPA patients into three subgroups. A principal component (PC) analysis aggregated 15 types of complements into alternative pathway-related PC 1 and complement classical pathway and common pathway-related PC 2. Conclusions: The serum levels of properdin and factor D were correlated with the BVAS and the VDI in MPA and GPA, respectively. Our analyses suggested the pathological heterogeneity of MPA and GPA from the aspect of complement components.